2022
DOI: 10.3390/ijms23147535
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Characterization of Histone Deacetylase 8 (HDAC8) Proteolysis Targeting Chimeras (PROTACs) with Anti-Neuroblastoma Activity

Abstract: In addition to involvement in epigenetic gene regulation, histone deacetylases (HDACs) regulate multiple cellular processes through mediating the activity of non-histone protein substrates. The knockdown of HDAC8 isozyme is associated with the inhibition of cell proliferation and apoptosis enhancement in several cancer cell lines. As shown in several studies, HDAC8 can be considered a potential target in the treatment of cancer forms such as childhood neuroblastoma. The present work describes the development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Even though most work on HDAC PROTACs has focused on HDAC6, 38 the first degraders of HDAC1, HDAC2, and/or HDAC3 utilizing a hydrazide or aminoanilide zincbinding group were recently disclosed. 24,28,36,37 Furthermore, in 2022, the first selective HDAC4 39 and HDAC8 27,29,40 PROTACs were reported. Interestingly, a chemoproteomics study by Xiong et al demonstrated that HDAC6 and HDAC3 are most amenable for targeted protein degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though most work on HDAC PROTACs has focused on HDAC6, 38 the first degraders of HDAC1, HDAC2, and/or HDAC3 utilizing a hydrazide or aminoanilide zincbinding group were recently disclosed. 24,28,36,37 Furthermore, in 2022, the first selective HDAC4 39 and HDAC8 27,29,40 PROTACs were reported. Interestingly, a chemoproteomics study by Xiong et al demonstrated that HDAC6 and HDAC3 are most amenable for targeted protein degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Subsequently, additional selective HDAC6 degraders were discovered based on the selective HDAC6i nexturastat A. , These findings raise the intriguing question, whether a selective or unselective HDAC6 ligand is superior to develop highly efficient and selective HDAC6 degraders. Even though most work on HDAC PROTACs has focused on HDAC6, the first degraders of HDAC1, HDAC2, and/or HDAC3 utilizing a hydrazide or aminoanilide zinc-binding group were recently disclosed. ,,, Furthermore, in 2022, the first selective HDAC4 and HDAC8 ,, PROTACs were reported. Interestingly, a chemoproteomics study by Xiong et al demonstrated that HDAC6 and HDAC3 are most amenable for targeted protein degradation …”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the potential anti-neuroblastoma activity of newly designed HDAC8 degraders was pursued by Darwish et al [ 189 ], due to the critical involvement of HDAC8 in this pathology. The developed PROTACs were designed starting from previously disclosed benzhydroxamic HDAC8 inhibitors [ 143 , 189 ]. Different E3 ligase ligands, including CRBN and VHL, were explored to evaluate how the target degradation would be affected.…”
Section: Multi-target Pharmacological Tools Acting On Hdac8mentioning
confidence: 99%
“…PROTAC 74 also showed strong hyperacetylation of SMC3, as opposed to the negative control bearing an ester in place of the hydroxamic acid motif. Treatment of neuroblastoma cells with PROTAC 74 also led to neuronal differentiation, as confirmed by neurite-like outgrowths and enhanced differentiated phenotype in microscopic analysis [ 189 ]. These results confirm the potential therapeutic application of HDAC8-degrading PROTACs in neuroblastoma and pave the way towards the future development of novel epigenetic degraders for the treatment of complex diseases.…”
Section: Multi-target Pharmacological Tools Acting On Hdac8mentioning
confidence: 99%
See 1 more Smart Citation